INSIGHT INTO SEQUENCE, SRTUCTURE AND HOMOLOGY MODELLING OF MITOCHONDRIAL CITRATE SYNTHASE OF HOMO SAPIENCE - CHITTRAN ROY, (International Journal of Pharma and Bio Sciences, 2015)
Citrate Synthase is an enzyme and most often responsible for catalyzing the first reaction of the citric acid cycle: the condensation of acetyle-CoA and oxaloacetate to form citrate. The protein sequence of mitochondrial citrate synthase having Uniprot Id O75390, has no 3D structure in protein data bank (PDB) till now. We know protein structure play an important role in their function. Our present work is based on primary and secondary structure analysis and production of high quality 3D structure of mitochondrial citrate synthase and its salt-bridge analysis. The protein was retrieved from UniProt date base. Physicochemical property has been calculated with the help of PHYSICO software. Homology modeling was performed by using MODELLER 9v11 and final model was then undergoing NAMD minimization and successfully passes through PROCHEAK, ERRAT, VERIFY-3D, Pro-Q and RAMPAGE. This model is successfully submitted in Protein Model Database having PMDB id PM0080060.